Pretomanid development and its clinical roles in treating tuberculosis. (December 2022) - Fekadu, Ginenus; Tolossa, Tadesse; Turi, Ebisa; Bekele, Firomsa; Fetensa, Getahun
Highlights: Tuberculosis (TB) is the leading infectious cause of mortality worldwide, and drug-resistant tuberculosis is often more difficult and costly to treat. Discovery of novel drugs and new methods of targeted drug delivery has the potential to improve the treatment outcome, lower the duration of treatment, and reduce adverse events. Based on the Nix-TB trial, pretomanid along with bedaquiline and linezolid was approved by the Food and Drug Administration and the World Health Organization for treating adult patients with treatment-intolerant or unresponsive drug-resistant TB. The effectiveness of pretomanid was reported in different observational and clinical studies; however, long-term safety data in humans are not yet available and the current regimen is recommended under an operational research framework. More research is needed before pretomanid can be celebrated as a promising candidate for the treatment of different categories of TB and specific patients. ABSTRACT: Tuberculosis (TB) is the leading infectious cause of mortality worldwide. Despite the development of different antituberculosis drugs, managing resistant mycobacteria is still challenging. The discovery of novel drugs and new methods of targeted drug delivery have the potential to improve treatment outcomes, lower the duration of treatment, and reduce adverse events. Following bedaquiline and delamanid, pretomanid is the third medicine approved as part of a novel drug regimen for treating drug-resistant TB. It is a promising drug that has the capacity to shape TB treatment and achieve the End TB strategy set by the World Health Organization. The effectiveness of pretomanid has been reported in different observational and clinical studies. However, long-term safety data in humans are not yet available and the pretomanid-based regimen is recommended under an operational research framework that prohibits its wider and programmatic use. Further research is needed before pretomanid can be celebrated as a promising candidate for the treatment of different categories of TB and specific patients. This review covers the update on pretomanid development and its clinical roles in treating Mycobacterium tuberculosis .